Highlighting Characteristics of CEFR-Based Digital Expository Reading Resource Needs: Menyoroti Karakteristik Kebutuhan Sumber Daya Bacaan Ekspositori Digital Berbasis CEFR - Nurushofi, Alviyah; Hidayat, Hendi; Noerjanah, Siti Luruh Ayu (Foreign Language Instruction Probe, 2024)
For most students, learning to read exposition text is not easy. When reading expository material, students often struggle to understand the purpose of reading, identify key concepts, and locate specific details in the text. These problems cause EFL (English as a Foreign Language) learners to find reading expository texts a challenging task. Since almost all students have difficulty understanding expository texts, teachers need strategies to facilitate their comprehension of such texts. One potential strategy is to incorporate CEFR (Common European Framework of Reference for Languages)-based digital reading resources into the EFL classroom. The use of these digital reading resources provides an opportunity for students to improve their English language skills and critical thinking. This study aims to identify the characteristics of CEFR-based expository digital reading resources in the EFL classroom. This study used an R&D (research and development) design with a qualitative approach. A needs analysis was conducted through interviews with two teachers who provided insights into what students need when learning using the internet. The results showed that digital resources are needed to help students learn expositional texts. These digital resources not only help in understanding expository texts but also play an important role in the development of students' overall English language skills and critical thinking skills.